Catalytic Mechanism of Aromatic Nitration by Cytochrome P450 TxtE: Involvement of a Ferric-Peroxynitrite Intermediate - Savvas Louka; Sarah M. Barry; Derren J. Heyes; M. Qadri E. Mubarak; Hafiz Saqib Ali; Lona M. Alkhalaf; Andrew W. Munro; Nigel S. Scrutton; Gregory L. Challis; Sam P. de Visser (American Chemical Society, 2024)
J. Am. Chem. Soc. 2020, 142, 15764−15779